Role of Memantine in the Management of Fibromyalgia: A Neuropharmacological Approach - Muhammad Adnan Aslam, Junaid Ur Rehman, Amna Tariq, Adnan Mahmood, Muhammad Junaid Munir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pharmacological treatment is one approach to managing fibromyalgia symptoms; however, selecting the appropriate medication is crucial to effectively minimizing patient discomfort. Objective: To assess the role of memantine in the management of fibromyalgia. Methodology: The study was ethically approved through the institutional review board. A cohort double blinded study was performed at Department of Neurology Services Institute of Medical Sciences, Services Hospital Lahore from 1st May 2023 to 31st October 2023. A total number of 200 patients were enrolled. The patients were confirmed cases of fibromyalgia and were within the age group of above 18 years. The diagnosis of fibromyalgia was done on the basis of clinical signs and symptoms. The patients were divided into two groups. Group memantine received maintenance dosage of memantine and group placebo (n=100) did not receive memantine. The patients who were receiving memantine got the dosage of 20 mg 1 tablet of 10 mg twice daily. The dose of 20 mg was titrated in a manner that patient received 5mg dose in week 1,10 mg in week 2, 15 mg in week 3 and 20 mg in week 4, continued as such till 12th week and were followed up for the outcomes. The follow-up of the patients (1st, 2nd week and at months) was planned up till a total of 3 month. A well-structured questionnaire was used for documenting the impact of the fibromyalgia through the administrated drug. Results: The Fibromyalgia was found in 80% of the cases as severe (both groups cumulative) followed by 16% patients having moderate disease severity and only 2% with mild disease condition. There were majority of the females observed within groups with a number of 93% and 94% in group memantine and group placebo respectively. The mean age of the patients within both groups was 37.6±1.2 and 38.4±1.3 years. Around 84% of the total patients had an improvement in their disease condition. Conclusion: Memantine administration improves the fibromyalgia condition and was observed to demonstrate positive outcomes in 84%of cases within 3 months as per FIQ scores. Keywords: Role, Memantine, Management, Fibromyalgia, Neuropharmacological approach